Fabrication of heteroatom-doped graphene-porous organic polymer hybrid materials via femtosecond laser writing and their application in VOCs sensing - Rasha Diab; Ganjaboy Boltaev; Mahmoud M. Kaid; Ahmad Fawad; Hani M. El-Kaderi; Mohammad H. Al-Sayah; Ali S. Alnaser; Oussama M. El-Kadri (Scientific Reports)
Abstract Graphene, a two-dimensional material featuring densely packed sp2-hybridized carbon atoms arranged in a honeycomb lattice, has revolutionized material science. Laser-induced graphene (LIG) represents a breakthrough method for producing graphene from both commercial and natural precursors via direct laser writing, offering advantages such as simplicity, efficiency, and cost-effectiveness. This study demonstrates a novel approach to synthesize a composite material exclusively from a porous organic polymer (POP) by direct femtosecond laser writing on a compressed imide-linked porous organic polymer substrate. The formation of the LIG on the substrate was identified using X-ray diffractometry (XRD) and Raman analysis, where the variation of the 2D peaks of the LIG was obtained. The resulting heterostructure, termed LIG@NI-POP, consists of a few-layered porous and conductive graphene engraved onto the surface of microporous polyimide. X-ray Photoemission Spectroscopy (XPS) confirmed the formation of a hierarchical porous hybrid material with high nitrogen (N) and oxygen (O) self-doping in the graphene. Leveraging its porosity, surface and bulk chemistry, and electrical properties, LIG@NI-POP was tested for sensing volatile organic compounds (VOCs) as a proof-of-concept application. The composite material exhibited dual functionality as a sensor and adsorbent for VOCs, demonstrating significant sensitivity and selectivity towards acetone over ethanol due to enhanced intermolecular interactions. This approach broadens the scope of laser direct writing to include various porous polymers, facilitating the fabrication of hybrid materials that integrate the unique properties of both graphene and porous polymers, thereby enhancing their potential applications in areas that leverage these synergistic properties.